EFFECT OF VISCOUS DAMPING IN NUMERICAL CALCULATION OF CABLE-MEMBRANE STRUCTURES BY THE METHOD OF DYNAMIC RELAXATION - Miloš Huttner; Petr Fajman (Acta Polytechnica CTU Proceedings)
The aim of this article is to assess the speed of convergence of numerical calculation of cable-membrane structures using dynamic relaxation method in the process of finding critical damping pre-calculated on undamped system. The procedure is tested on four different constructions in six numerical cases. The variety of examples is as large as possible to demonstrate the greatest versatility of the test procedure. The efficiency of the procedure is evaluated based on the number of iterations.